The impact of incentives on prosumers knowledge sharing – the dimension of their characteristics - Eisenbardt, Monika (Wpływ zachęt na dzielenie się wiedzą prosumentów przez pryzmat ich cech demograficznych, 2019)
One of the most important challenges for enterprises is to engage prosumers in knowledge sharing. This problem is addressed by incentives which can encourage prosumers to share knowledge. The aim of this paper is to examine prosumers need for incentives to share knowledge. The reported outcomes are the result of the questionnaire survey that yielded responses from 783 prosumers. The results show that prosumers need incentives to share knowledge. The statistical analyses indicated that there were significant differences between prosumers with different education level whilst there were no significant differences between females and males as to incentives needed by them to engage in knowledge sharing. The analysis of different generations shows that there were significant differences between age generations, especially between the youngest (Z generation) and the oldest ones (Builders and Baby-Boomers combined generations). What is more, the results show that prosumers do need incentives. Only less than 10% of prosumers indicated that they do not need incentives to engage in knowledge sharing. This suggests that prosumers, regardless their gender, education level, and age, pay attention to incentives and without them, they are not willing to share knowledge with businesses
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 2 (52), s. 41-57
Keywords: incentives; consumer; prosumer; generations; zachęty; konsument; prosument; pokolenia